2022
DOI: 10.4414/smw.2022.w30173
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies and associated risk factors in children less than 6 years of age in the canton of Fribourg, Switzerland (COVPED study): a population-based cross-sectional study

Abstract: BACKGROUND: To date, few data are available about severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seroprevalence in young children and the role of early-life childcare arrangements in transmission of the virus. In this study, we assessed the SARS-CoV-2 seroprevalence in children less than 6 years of age in the canton of Fribourg and identified risk factors associated with seropositivity. METHODS: The COVPED study is a population-based cross-sectional study in children less than 6 years of age livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Although an increased number of household members did not affect the risk of seropositivity in children, we found that a higher risk of seropositivity was observed in children living with infected household members than those living with non-infected household members. This finding was consistent with a study from Switzerland that indicated the risk of being seropositive in children aged <6 years was more likely associated with the number of household members who tested positive for SARS-CoV-2, indicating the SARS-CoV-2 transmission for children aged <6 years occurs commonly within the family [ 20 ]. In addition, our study was consistent with previous reports in Uganda that reported no significant difference in infection-induced seropositivity based on the gender of the study participants [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although an increased number of household members did not affect the risk of seropositivity in children, we found that a higher risk of seropositivity was observed in children living with infected household members than those living with non-infected household members. This finding was consistent with a study from Switzerland that indicated the risk of being seropositive in children aged <6 years was more likely associated with the number of household members who tested positive for SARS-CoV-2, indicating the SARS-CoV-2 transmission for children aged <6 years occurs commonly within the family [ 20 ]. In addition, our study was consistent with previous reports in Uganda that reported no significant difference in infection-induced seropositivity based on the gender of the study participants [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, recent studies have shown that the continuation of the epidemic with new SARS-CoV-2 variants and shifts in preventive measures and vaccination changed the situation [ [88] , [89] , [90] , [91] ]. In addition, it seems that transmission between family members seemed more important than transmission within day care centres [ 87 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…seropositive in children aged <6 years was more likely associated with the number of household members who tested positive for SARS-CoV-2, indicating the SARS-CoV-2 transmission for children aged <6 years occurs commonly within the family[15].The proportion of anti-N IgG or anti-RBD antibody seropositive among unvaccinated and anti-N IgG seropositive among vaccinated cases may reflect the true rate of infections, including mildly symptomatic or asymptomatic cases and undetected by COVID-19 testing. Our study found that 35.9% children aged 5-7 years with seropositivity reported no previous infection.This result may reflect either asymptomatic infection or undetected infection upon COVID-19…”
mentioning
confidence: 99%